LITERASI KEUANGAN MASYARAKAT KOTA METRO TERHADAP PRODUK INVESTASI PADA ASURANSI SYARI’AH DAN DEPOSITO SYARI’AH - Rina El Maza (Adzkiya : Jurnal Hukum dan Ekonomi Syariah, 2017)
This paper examines the financial literacy of the citizens of Metro City for investment products in Sharia Insurance and Sharia Deposit. Financial literacy is reviewed by distributing questionnaires to 100 Metro City citizens. The result of descriptive analysis of respondent literacy for financial management is moderate with percentage 72%. The value is between 60% <80%. Then the literacy of respondents for sharia insurance is also in a moderate position with a percentage of 73%. As for syariah deposits only 49% (low).